2015
DOI: 10.5152/tjg.2014.5229
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effects of massive bowel resection on liver function and hepatocyte apoptosis

Abstract: Background/Aims: The effects of short-bowel syndrome on liver function and liver morphology independent of parenteral nutrition have not been thoroughly investigated. Our aim was to investigate the effects of massive bowel resection on hepatocyte apoptosis and liver function in rats. Materials and Methods: A total of 37 female Sprague-Dawley rats were randomly assigned to five groups: Control (no procedure); Sham 1 [laparotomy (LT)/enterotomy (ET); evaluated on postoperative day (POD) 1]; Sham 2 (LT/ET; evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Clinical or experimental studies that have investigated the mechanism of sepsis in MBR patients without PN suggested that MBR without PN is a proinflammatory state and the increased production of proinflammatory cytokines may result in liver damage in sepsis (27,28). It has been shown that massive bowel resection alone can cause liver pathologies but the underlying molecular mechanism has not been elucidated (14). However, O'Brien et al have proposed that massive small-bowel resection may cause bacterial translocation in animals which may lead to repeating episodes of sepsis but the precise mechanism for bacterial translocation after massive small bowel resection is currently unknown (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical or experimental studies that have investigated the mechanism of sepsis in MBR patients without PN suggested that MBR without PN is a proinflammatory state and the increased production of proinflammatory cytokines may result in liver damage in sepsis (27,28). It has been shown that massive bowel resection alone can cause liver pathologies but the underlying molecular mechanism has not been elucidated (14). However, O'Brien et al have proposed that massive small-bowel resection may cause bacterial translocation in animals which may lead to repeating episodes of sepsis but the precise mechanism for bacterial translocation after massive small bowel resection is currently unknown (29).…”
Section: Discussionmentioning
confidence: 99%
“…Sterile 10 ml saline which was kept warm was administered into the peritoneal cavity for postoperative fluid balance, and 4-0 silk was used to suture the abdomen. Rats in the sham MBR received a laparotomy operation with enterotomy and anastomosis was performed (14).…”
Section: Methodsmentioning
confidence: 99%